Association between air pollution exposure and lower urinary tract symptoms in Korean men - Young Min Jee; Seo Eun Hwang; Jae Moon Yun; Su Hwan Cho; Soon Tae Kim; Yoon Hee Kang; Hyun Jin Kim; Jin Ho Park (Scientific Reports)
Abstract The purpose of this study was to investigate the association between long-term air pollution exposure and Low Urinary Tract Symptoms (LUTS) in Korean men. This study included 7,979 adult men who underwent health checkups. Each subject’s annual average air pollution exposure levels were estimated using the Community Multiscale Air Quality model. LUTS were evaluated using the International Prostate Symptom Score (IPSS) questionnaire, and the IPSS values were analyzed for their association with LUTS severity. The study population had an average age of 56.1 years, with a prevalence of LUTS at 39.8%. None of the air pollutants were significantly associated with overall LUTS prevalence after adjusting for potential confounders. Interestingly, when divided into two symptoms of LUTS, exposures to particulate matter ≤ 2.5 μm in diameter (PM2.5) and particulate matter ≤ 10 μm in diameter (PM10) were significantly associated with an increased prevalence of voiding symptoms, but not with storage symptoms. Regarding the LUTS severity, PM2.5 and sulfur dioxide (SO2) exposures were closely related to an increased severity of overall LUTS. We report for the first time that long-term exposure to ambient air pollution, such as particulate matter, is associated with a higher prevalence and severity of LUTS, particularly voiding symptoms.